The Training Curriculum Development for Enhancing Digital Technology for Learning Management Abilities of Vocational College Lecturers in Jiangsu Province, People’s Republic of China - Weifang, Yu; Prachanant , Nawamin; Buranaphansak, Ketsuda (Journal of Roi Kaensarn Academi, 2024)
Ability to manage the digital technology for teaching and learning is the first priority for vocational college lecturers in the present time. This study aimed: 1) to analyze current situations and needs on digital technology for learning management abilities of vocational college lecturers; 2) to design and develop the training curriculum for enhancing digital technology for learning management abilities of vocational college lecturers; 3) to implement the training curriculum for enhancing digital technology for learning management abilities of vocational college lecturers；and 4) to evaluate the training curriculum for enhancing digital technology for learning management abilities of vocational college lecturers in Jiangsu Province, Peoples’ Republic of China. This study was divided into four phases: Phase 1 Studying and analyzing the current situations and needs on digital technology for learning management abilities of vocational college lecturers. The samples were 100 lecturers, 100 students and 100 graduates from Wuxi Vocational College of Science and Technology. A questionnaire was designed to assess the digital technology for learning management abilities of vocational college lecturers. The collected data were analyzed by using frequency, percentage, mean and standard deviation; Phase 2 Developing the training curriculum. The target group consisted of 20 stakeholders, including one director, one vice director, 8 department heads, and 10 employers. Content analysis technique was performed on the interview data; Phase 3 Implementing the training curriculum. The target group included 10 lecturers who volunteered to participate in the training curriculum in Wuxi Vocational College of Science and Technology. The instrument was training process module testing and post-training following-up survey. The collected data were analyzed by using frequency, percentage, mean and standard deviation; Phase 4 Evaluating the training curriculum. The target groups were 10 vocational college lecturers and five experts. The research instruments were satisfaction questionnaire and questionnaire for evaluating the quality of the training curriculum. The data were analyzed by using mean and standard deviation. The findings could be summarized as follows: 1. The digital technology for learning management abilities of vocational college lecturers included four factors: Digital application, Digital technology Knowledge and skills, Digital awareness, Professional development, which Digital awareness was at a high level while Digital application, Digital technology knowledge and skills, Professional development were at a moderate level. 2. The designed and developed training curriculum included three modules: Digital application, Digital technology knowledge and skills, Professional development. Each module spanned 16 hours, resulting in a comprehensive 6 days and 48 hours. The training curriculum comprised both theoretical learning and practical exercises. 3. The results of the training curriculum showed that the digital technology for learning management abilities of vocational college lecturers was higher after the training of Module 1 Digital application, Module 2 Digital technology knowledge and skills and Module 3 Professional development and the skill application rate reached 82.80%. The training curriculum was effective and feasible. 4. The lecturers from Wuxi Vocational College of Science and Technology were satisfied towards the training curriculum for enhancing digital technology for learning management abilities at a high level. In addition, the experts rated the quality of the training curriculum in overall was at a high level. When considering each quality component, it was found that the highest mean score was the quality of feasibility, followed by propriety, utility, accuracy, and comprehensiveness.